The experience of absurdity: existentialistic paradigm and paradigm of theatre of the absurd (with regard to Samuel Becket's play 'Not I') - H. O. Verbivska, (Ukrainian Cultural Studies, 2021)
This article circles around the phenomenon of absurdity and absurd which appears to be greatly elaborated by Albert Camus and Theatre of the Absurd. The article reflects mainly upon Becket's dramatic monologue "Not I", which might be characterized as a sort of missing link between two forms of absurd. The style of Albert Camus puts emphasis on the inner experience extrapolated by means of the author. In this sense, the feeling of despair and existential crisis, typical for existentialism in general, brings into existence the absurdity of being as such. In comparison with that, the manner, in which Theatre of the Absurd presents current states of things, organizes the comic dimension of a given situation. To put it another way, Theatre of the Absurd sets up living intersubjectivity, which is a sense-formative precondition of the laughter, and dynamic omnipresence of the inner experience literally declared on the scene. Becket's "Not I" deploys, on the one hand, the existentialistic understanding of human beings, and, on the other, the theatrical representation injected with intersubjectivity. The article takes into account Deleuzian approach towards cinematography in order to conceptualize Becket's play. The notion of affection-image, which is taken from Deleuze, illustrates the structure and essentially the nature of images taking place in "Not I". Becket draws special attention to the image of the voice with regard to audial metaphors, which the main heroine uses during all the time of self-enunciation. Behind the words that she speaks there is an implicit trauma, which is unknown to the contemplators of the performance. It is noteworthy to admit that the organization of the play makes visible only the mouth of the heroine whereas everything remains in the shadows. Deleuzian affection-image deals with annihilated spatial-temporal coordinates and absolutization of the face (faceification). The quality of metaphors in the monologue and the decoration of space establish the phenomenon of absurdity in Becket's "Not I".
Keywords: absurd, affection-image, laughter, spatial-temporal coordinates